Borrowing in Tabeldit, the Berber Speech of Igli Speech Community - Mouili, Fatiha (LANGUAGE ART, 2022)
This paper analyzes the phenomenon of borrowing in one of Berber varieties spoken in the southern part of Algeria. Borrowing is one the most important sociolinguistic phenomena which exists in all the language varieties. The Berber variety which is analyzed in this paper is named “Tabeldit” and it is spoken in the area of “Igli” which is located in Bechar. Data analysis and results in this paper are based on the primary data which were collected from questionnaires and interviews. In fact, the loan words which are found in ‘Tabeldit’ are not taken from Standard Arabic or the Algerian dialect, particularly the one used in Bechar, but also from the French language.